2019
DOI: 10.1177/2040620718816698
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy combinations in acute myeloid leukemia: what are the options?

Abstract: Epigenetics refers to the regulation of gene expression mainly by changes in DNA methylation and modifications of histone proteins without altering the actual DNA sequence. While epigenetic modifications are essential for normal cell differentiation, several driver mutations in leukemic pathogenesis have been identified in genes that affect epigenetic processes, such as DNA methylation and histone acetylation. Several therapeutic options to target epigenetic alterations in acute myeloid leukemia (AML) have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 153 publications
1
63
1
5
Order By: Relevance
“…While these findings require further investigation, it is possible that HDJ2 regulates histone properties. Interestingly, both of the protein synthesis inhibitors (bortezomib and omacetaxine) in our screen were antagonistic to HDJ2 depletion [67]. We confirmed that omacetaxine (protein biosynthesis inhibitor) displayed reduced potency upon inhibition of HDJ2 [42].…”
Section: Discussionsupporting
confidence: 64%
“…While these findings require further investigation, it is possible that HDJ2 regulates histone properties. Interestingly, both of the protein synthesis inhibitors (bortezomib and omacetaxine) in our screen were antagonistic to HDJ2 depletion [67]. We confirmed that omacetaxine (protein biosynthesis inhibitor) displayed reduced potency upon inhibition of HDJ2 [42].…”
Section: Discussionsupporting
confidence: 64%
“…Epigenetically based combination therapies are recently showing more promising curative results than monotherapies in several cancer types [33,[53][54][55]. The maximum pharmacodynamic effect of a drug, including an HDAC or a DNMT inhibitor, will be limited by the toxicity of the provided dose.…”
Section: Discussionmentioning
confidence: 99%
“…Several targeted epigenetic therapies have been explored for AML, for example, hypomethylating agents (HMA), histone deacetylase (HDAC) inhibitors, and IDH1/2 inhibitors. However, as monotherapy these inhibitors do not seem to be effective, and treatment failure is common [250][251][252][253]. To potentiate the efficacy of epigenetic therapy, combination strategies with cytotoxic chemotherapy or other targeted drugs are currently being extensively studied.…”
Section: Pi3k/akt/mtor Inhibitors In Combination With Epigenetic Targmentioning
confidence: 99%